Environmental awareness and consumption habits among university students - Berrío-Quispe, Margoth Luliana; Chávez-Bellido, Dina Emeteria; Aguilar-Mori, Karim (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The aim of the study was to assess the level of relationship between environmental awareness and consumption habits among second-cycle general studies students at a private university in Lima in 2023. It is a basic research with a quantitative approach, a non-experimental cross-sectional design, correlational scope, and a hypothetical-deductive method. The non-probabilistic sample of 150 students used a survey to measure the level of environmental awareness with dimensions: affective, cognitive, conative, and active; and for consumption habits with dimensions: irresponsible consumption and responsible consumption. The results indicate that the level of environmental awareness "almost always" and "always" is 48,7 % and 46,7 %, respectively, meaning that the majority of students have a good level of environmental awareness. Additionally, there is a significant relationship between environmental awareness and consumption habits, demonstrating a positive correlation in students’ behavior with respect to their environment.